A strange book of incomprehensible nonsense : or how I became an intertemporal avant-garde artist and went completely batshit insane : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Cauchi, David (Massey University, 2012)
This exegesis is an account of the author’s time-travel trip to meet the 15th century painter Piero della Francesca. It complements the thesis for this project, which consists of two sets of paintings: ‘Before meeting Piero’ and ‘After meeting Piero’. Piero is first visited in 1437, just after he had been commissioned to paint The Baptism of Christ. The exegesis contains a close analysis of Piero della Francesca’s painting The Baptism of Christ, the circumstances of its commissioning, and the factors in Piero’s personality and background that determined its form and content. The exegesis presents an original geometric analysis of the pictorial construction of Piero’s Baptism and shows how and why Piero developed it. Piero’s Baptism is presented as an example of an intertemporal avant-garde art work. The exegesis defines the intertemporal avant-garde as an ahistorical phenomenon, where structural affinities are more important than relative spacetime co-ordinates. As demonstrated in the exegesis, the defining feature of the avant-garde is antagonism, especially towards academic and official art institutions. The exegesis also discusses the author’s intertemporal avant-garde movement, common-sense nihilism.
Keywords: David Cauchi; Piero della Francesca; Criticism and interpretation; Nihilism in art; Avant-garde art